Insights into Enhancing Rural Service Quality through Community-Driven Research: Wawasan untuk Meningkatkan Kualitas Layanan Pedesaan melalui Penelitian Berbasis Masyarakat - Pratama, Yoga Putra Nur; Fitria Agustina, Isna (Universitas Muhammadiyah Sidoarjo, 2024)
This research analyzes the quality of population administration services in Kejapanan village, Gempol District, Pasuruan Regency, focusing on both inhibiting and supporting factors. Using a descriptive qualitative approach, data were gathered through interviews, observations, and documentation with village officials and community users. Findings indicate deficiencies in service facilities, reliability due to established standards, responsiveness through a suggestion box, inadequate punctuality, and strong empathy from officials. Challenges include human resource quality and employee discipline, while training supports service improvements. Enhancing facilities, discipline, and training are recommended to boost service quality. Highlights: Service Deficiencies: Gaps in facilities, infrastructure, and punctuality impact quality. Officer Reliability: Established standards ensure reliable administration and service support. Community Interaction: Responsiveness and empathy foster positive community relations. Keywords: population administration, service quality, village governance, qualitative research, community satisfaction